SAT0401 Antiphospholipid Antibodies in Lupus Nephritis and Their Role in Long-Term Outcome. (9th June 2015) - Parodis, I.; Svenungsson, E.; Gerhardsson, J.; Zickert, A.; Malmström, V.; Gunnarsson, I.
Abstract : Background: Lupus nephritis (LN) is a major manifestation of Systemic Lupus Erythematosus (SLE). The burden of antiphospholipid antibodies (APLA) in LN has not been clarified. Objectives: We investigated a potential role of APLA levels as a biomarker of severity in renal lupus. Methods: Serum levels of APLA (antibodies to cardiolipin (aCL) and β2 -glycoprotein 1 (anti-β2 -GP1); reference values <20 IE/mL) were assessed by BioPlex 2200 in a cross-sectional cohort of 508 SLE patients, as well as in 64 patients with biopsy-ascertained active LN (52 proliferative, 12 membranous) before and after induction treatment. Follow-up renal biopsies were performed in 63 patients. Patients were followed for a mean time of 10.9 years (range 3.3–18.8). The outcome of kidney function and damage was assessed according to a chronic kidney disease (CKD) grading system based on the estimated glomerular filtration rate, as determined by the Modification of Diet in Renal Disease Study equation. Clinical responders (CR) were required to have ≥50% reduction in proteinuria, normal or improved renal function and inactive urinary sediment. Histopathological responders (HR) were required to have ≥50% improvement in Activity Index. Results: Percentages of APLA positive patients in the active LN cohort at baseline (aCL: 12.5% IgG, 9.4% IgM; anti-β2 -GP1: 20.3% IgG, 9.4% IgM) were comparable to the ones in the cross-sectional SLE cohort (entire cohort: 20.1% IgG, 7.1% IgM aCL, 21.3% IgG, 7.3% IgM anti-β2 -GP1; patients with renal involvement, n=200: 22.5% IgG, 6% IgM aCL, 24% IgG, 6.5% IgM anti-β2 -GP1; patients without renal involvement, n=295: 18.6% IgG, 8.1% IgM aCL, 19.7% IgG, 8.1% IgM anti-β2 -GP1), but lower in the LN cohort following induction treatment (aCL: 9.4% IgG, 1.6% IgM; anti-β2 -GP1: 10.9% IgG, 3.1% IgM). APLA titers showed significant decreases following treatment (p<0.001 in all LN subgroups). In patients with proliferative LN, IgM titers decreased significantly in responders (CR, n=41: p=0.002 for aCL, p=0.004 for anti-β2 -GP1; HR, n=43: p=0.001 for aCL, p=0.002 for anti-β2 -GP1) but not in non-responders. IgG titers decreased significantly in all response groups, with the exception of IgG aCL in clinical non-responders (p=0.068). In the membranous LN subgroup, APLA levels remained unchanged regardless of treatment outcome. IgM titers decreased significantly in all treatment groups. IgG titers decreased significantly in patients given cyclophosphamide and mycophenolate mofetil, but remained unchanged in rituximab-treated patients. CKD stage at discharge correlated significantly with the duration of follow-up (p=0.15, r=0.3) but did not correlate with either APLA levels or positivity. Conclusions: APLA levels were comparable in SLE patients with or without renal involvement and in patients with active LN, but decreased significantly following induction therapy given for LN. In proliferative LN, IgG and IgM titers were affected differently by immunosuppression with regard to treatment response: IgG titers decreased regardless of treatment outcome while IgM decreased only in responding patients. As expected, renal damage increased with disease duration; however, neither APLA levels nor positivity correlated with long-term renal outcome. Investigation of the association between APLA and treatment response in larger LN cohorts might give further insight. Disclosure of Interest: None declared